2020
DOI: 10.3390/ijms21249420
|View full text |Cite
|
Sign up to set email alerts
|

Congestive Hepatopathy

Abstract: Liver disease resulting from heart failure (HF) has generally been referred as “cardiac hepatopathy”. One of its main forms is congestive hepatopathy (CH), which results from passive venous congestion in the setting of chronic right-sided HF. The current spectrum of CH differs from earlier reports with HF, due to ischemic cardiomyopathy and congenital heart disease having surpassed rheumatic valvular disease. The chronic passive congestion leads to sinusoidal hypertension, centrilobular fibrosis, and ultimatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 125 publications
0
47
1
Order By: Relevance
“…The widespread use of heart transplantation (HT) and considerable breakthroughs in medical and surgical treatments have drastically altered the profile of CH patients. As a result, compared to previous reports, cardiac cirrhosis due to noncongenital HF is decreasing, ischemic cardiomyopathy has superseded rheumatic HF as the primary cause of HF, and CH following Fontan surgery is increasing [3].…”
Section: Fig 2 Liver Outcomes Following Heart Transplantmentioning
confidence: 79%
See 2 more Smart Citations
“…The widespread use of heart transplantation (HT) and considerable breakthroughs in medical and surgical treatments have drastically altered the profile of CH patients. As a result, compared to previous reports, cardiac cirrhosis due to noncongenital HF is decreasing, ischemic cardiomyopathy has superseded rheumatic HF as the primary cause of HF, and CH following Fontan surgery is increasing [3].…”
Section: Fig 2 Liver Outcomes Following Heart Transplantmentioning
confidence: 79%
“…Development of cirrhosis and eventually cirrhosis of the liver may occur, with associated risks of liver failure and hepatocellular carcinoma. This risk is likely to increase over the course of the patient's life [3,[8][9][10] (Fig. 2).…”
Section: Fig 2 Liver Outcomes Following Heart Transplantmentioning
confidence: 99%
See 1 more Smart Citation
“…One of its main forms is congestive hepatopathy (CH), consisting of venous congestion associated with right-sided HF. The chain of events determined by chronic passive congestion is represented by sinusoidal hypertension, centrilobular fibrosis, cirrhosis, and even carcinogenesis (hepatocellular carcinoma) [ 81 ]. In another study, miR-122, the predominant miRNA in the liver [ 82 ], was indicated to be essential for liver homeostasis, while its loss resulted in promoting liver steatosis, inflammation, fibrosis, and even carcinogenesis [ 82 84 ].…”
Section: Personalized Medicine In Heart Failurementioning
confidence: 99%
“…Currently, the commonly used methods for evaluating the severity and prognosis of patients with liver failure are mostly based on the functions of multiple organs themselves. [14][15][16][17] But this method has limitations in terms of accuracy and convenience of application. Hormones play an important role in body metabolism and organ function regulation.…”
Section: Introductionmentioning
confidence: 99%